2015
DOI: 10.1124/dmd.115.065714
|View full text |Cite
|
Sign up to set email alerts
|

Drug Metabolism by the Host and Gut Microbiota: A Partnership or Rivalry?

Abstract: The importance of the gut microbiome in determining not only overall health, but also in the metabolism of drugs and xenobiotics, is rapidly emerging. It is becoming increasingly clear that the gut microbiota can act in concert with the host cells to maintain intestinal homeostasis, cometabolize drugs and xenobiotics, and alter the expression levels of drug-metabolizing enzymes and transporters and the expression and activity levels of nuclear receptors. In this myriad of activities, the impact of the microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(103 citation statements)
references
References 67 publications
1
96
0
6
Order By: Relevance
“…Our study identified significant systemic toxicity to 4‐NQO in germ‐free mice (Figure C), suggesting that the absence of a microbiome significantly reduced drug‐metabolizing ability. This observation is consistent with previous reports that demonstrate that the gut microbiome plays an important role in drug metabolism . Moreover, colonization of germ‐free mice has been shown to significantly alter liver metabolic function including changes in expression and activity of major drug‐metabolizing enzymes .…”
Section: Resultssupporting
confidence: 92%
“…Our study identified significant systemic toxicity to 4‐NQO in germ‐free mice (Figure C), suggesting that the absence of a microbiome significantly reduced drug‐metabolizing ability. This observation is consistent with previous reports that demonstrate that the gut microbiome plays an important role in drug metabolism . Moreover, colonization of germ‐free mice has been shown to significantly alter liver metabolic function including changes in expression and activity of major drug‐metabolizing enzymes .…”
Section: Resultssupporting
confidence: 92%
“…The intestinal microbiota consist mainly of anaerobic bacteria, and they secrete a diverse array of enzymes that participate in drug biotransformation such as reduction, deconjugation, acetylation, deacetylation and N-demethylation [23,24]. Thus, the intestinal microbiota is important to the metabolism of orally ingested drug and xenobiotics.…”
Section: The Metabolism Of Ziyuglycoside I In Intestinal Flora (If)mentioning
confidence: 99%
“…The predose metabolomic profile of a drug may predict its postdose toxicity or efficacy, suggesting environmental influences and the role of the gut microbiome . The gut microbiome can influence an individual's metabolome and thus the drug metabolism and its pharmacologic response . To what extent and how postdose drug metabolites and safety relate to predose metabolites is unknown.…”
Section: Gut‐liver Microbiome Role In Drug Metabolism and Toxicitymentioning
confidence: 99%